2018
DOI: 10.1016/j.nima.2017.12.078
|View full text |Cite
|
Sign up to set email alerts
|

Bulk and surface event identification in p-type germanium detectors

Abstract: The p-type point-contact germanium detectors have been adopted for light dark matter WIMP searches and the studies of low energy neutrino physics. These detectors exhibit anomalous behavior to events located at the surface layer. The previous spectral shape method to identify these surface events from the bulk signals relies on spectral shape assumptions and the use of external calibration sources. We report an improved method in separating them by taking the ratios among different categories of in situ event … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 29 publications
(79 reference statements)
1
18
0
Order By: Relevance
“…Additionally, a method using alternately biased electrodes on each surface of the detectors, including the sides, has enabled the measurement of volume-only events, eliminating near-surface events related to low-energy particles strongly interacting with the medium [46]. Other techniques have been developed [53] to solve this problem.…”
Section: Dark Matter Direct Detection and Related Studiesmentioning
confidence: 99%
“…Additionally, a method using alternately biased electrodes on each surface of the detectors, including the sides, has enabled the measurement of volume-only events, eliminating near-surface events related to low-energy particles strongly interacting with the medium [46]. Other techniques have been developed [53] to solve this problem.…”
Section: Dark Matter Direct Detection and Related Studiesmentioning
confidence: 99%
“…It has been shown that the background and calibration sources data share the common bulk or surface rise-time distribution probability density function (PDF) [21]. The ratio method has been developed accordingly to address the BS discrimination problem in pPCGe [10,21].…”
mentioning
confidence: 99%
“…It has been shown that the background and calibration sources data share the common bulk or surface rise-time distribution probability density function (PDF) [21]. The ratio method has been developed accordingly to address the BS discrimination problem in pPCGe [10,21]. In this analysis, the inputs of the ratio method include the background data and three calibration samples ( 137 Cs, 60 Co, It has been verified with simulations using realistic detector electric field that these EFEs mainly originate from the region in the vicinity of the p + point electrode.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Energy calibrations were done by the zero energy (defined by the random trigger events) and the internal cosmogenic K-shell x-ray peaks: 8.98 keVee of 65 Zn and 10.37 keVee of 68;71 Ge. The data preprocessing procedures for a single detector were described in previous papers [26,27], including energy calibrations, pedestal cut, physics event selection, and bulk or surface event discrimination [28]. The live times were reduced by 1.1% for C10-B1 and 0.6% for C10-C1 after pedestal cuts, which were energy independent and measured by the survival of the random trigger events.…”
mentioning
confidence: 99%